Employing Typologies of Learning for a Holistic Evaluation of ServiceLearning Students - Oracion, Enrique G. (Silliman Journal, 2022)
Service-learning as a teaching strategy is popular in the Philippines because it serves the instruction, research, and extension or community engagement functions of higher education institutions. But it is also controversial because it is too demanding to students in terms of time and effort given their other school activities and requirements. It is, therefore, unfair for students if they are not fairly or realistically evaluated commensurate to the resources they put into the service of the community and the corresponding learning they generated if no deliberate plan and systematic procedure are followed by teachers. The community engagement model of Butin (2007) that is linked to the typologies of learning goals which include technical, cultural, political and anti-foundational is relevant for this purpose. This paper recommends that these learning goals constitute what the teachers should consider for giving grades to students and the weight for each type to the total grade shall depend upon the nature of the courses or subjects where service-learning is employed. Holistic evaluation of service learning students considers all types of learning they experience in community service which are not only evident in their activity reports but are made visible in the reflection sessions. The ten principles of service-learning by Howard (1993) are also excellent guides for appropriately, fairly and holistically evaluating service-learning students.